2003
DOI: 10.1038/sj.bjc.6601036
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced effects of aminolaevulinic acid-based photodynamic therapy through local hyperthermia in rat tumours

Abstract: The possibility of enhancing aminolaevulinic acid (ALA)-based photodynamic therapy (PDT) by simultaneous application of localised hyperthermia (HT) was evaluated. Treatments of rat DS-sarcomas included: (i) control, (ii) ALA administration (375 mg kg À1 , i.p.), no illumination, (iii) 'nonthermal' illumination, (iv) ALA-PDT: that is, ALA administration, 'nonthermal' illumination, (v) localised HT, 431C, 60 min (vi) ALA-PDT þ HT: ALA administration with full spectrum irradiation resulting in ALA-PDT and HT. Tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 42 publications
2
26
0
2
Order By: Relevance
“…PDT has the potential to be a powerful treatment modality for cancer either applied solitary or in combination with chemotherapy (16), surgery (17), radiotherapy (18), or other strategies, such as hyperthermia (19). However, low selectivity, inconveniently long drug-light intervals, and prolonged generalized photosensitivity are problems encountered with this therapy modality.…”
Section: Discussionmentioning
confidence: 99%
“…PDT has the potential to be a powerful treatment modality for cancer either applied solitary or in combination with chemotherapy (16), surgery (17), radiotherapy (18), or other strategies, such as hyperthermia (19). However, low selectivity, inconveniently long drug-light intervals, and prolonged generalized photosensitivity are problems encountered with this therapy modality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the effectiveness of HT combined with other therapies, especially radiotherapy, has been confirmed. Several studies have been performed with combination therapy of HT and PDT for malignant tumors and non-neoplastic diseases, suggesting the effectiveness of HT in combination therapy (11)(12)(13)(14)17,28,29).…”
Section: -------------------------------------------------Table IV Smentioning
confidence: 99%
“…Furthermore, it has been shown that wIRA reduces pain in chronic wounds, warts, herpes, scleroderma, gonarthrosis and spondylitis (Fuchs et al, 2004; Hartel et al, 2006). Applying wIRA would enhance the effects of PDT since heating has some synergistic effect when applied together with PDT (Waldow et al, 1985;Kelleher et al, 2003;Yanase et al, 2006). The use of antimicrobial PDT (APDT) could therefore potentially improve the tissue healing process in a number of dental procedures.…”
Section: Introductionmentioning
confidence: 99%